Socio-demographic Pictures of Under-Five Malnourished Children in a Tertiary Care Hospital (TAJ: Journal of Teachers Association, 2018)
This study was a cross-sectional descriptive type of study, conducted at Pediatrics department of Rajshahi Medical College Hospital from July 2014 to June 2016. A total 382 children were enrolled by purposive sampling among which 219 (57.3%) male, 163 (42.7%) female. The aim of this study was identify demographic as well as social status of malnourished children in tertiary care hospital. In this study the prevalence of underweight 42% (moderate & severe), wasting 34% (moderate & severe), and stunting 24% (moderate & severe) were found. Considering various Socio-demographic characteristics - maternal factors, paternal factors, socioeconomic status, and residential status had significant association with nutritional status of the children. Beside these various risk factors- birth weight, exclusive breast feeding, colostrum feeding, timing of weaning practices, type of complementary feeding and associated morbidities also had significant association with nutritional status of the children. The degree of malnutrition was found to more prevalent in the early age of children. Among the studied children more than half (60.5%) lived in rural area and rest of them lived in urban area (36.6%), semi urban area (2.9%) respectively. Children more than half (53%) were from lower class family. Rest of them was middle class (40.6%) and upper class (6.3%) family. Education level of the majority (59.4%) mother were primary to SSC, (22.5%) were below primary and (18.1%) were HSC and above. Education level of the majority ie.40.6% father were below primary, 39.8% were primary to SSC and 19.6% were HSC and above.TAJ 2017; 30(1): 56-60